Gold Nanoparticles - Reaching New Heights 2019
DOI: 10.5772/intechopen.80052
|View full text |Cite
|
Sign up to set email alerts
|

Red or Blue? Gold Nanoparticles in Colorimetric Sensing

Abstract: Gold nanoparticles (AuNPs) have been extensively used for the design of colorimetric sensors and probes due to their interesting photophysical properties. In particular, their surface plasmon resonance (SPR) is influenced not only by the size but also by the shape or the properties of the matrix surrounding the nanoparticles. This SPR band is sensitive to the proximity of other nanoparticles, and thus, analyte-triggered aggregation of AuNPs results in an important bathochromic shift of the SPR band and a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…53 The aggregation or disaggregation of colloidal gold nanoparticles in solution caused the changes in the surface plasmon absorption band. 56 This can be conveniently utilized to convert the recognition of molecules at a molecular level into a measurable signal, i.e., the color change. 56 The color change from red to blue is characteristic of using AuNPs for colorimetry, even in unmodied AgNPs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…53 The aggregation or disaggregation of colloidal gold nanoparticles in solution caused the changes in the surface plasmon absorption band. 56 This can be conveniently utilized to convert the recognition of molecules at a molecular level into a measurable signal, i.e., the color change. 56 The color change from red to blue is characteristic of using AuNPs for colorimetry, even in unmodied AgNPs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…[195] Such plasmonic coupling mediated colorimetric sensing has since been studied extensively and further enhancement by the incorporation of modern optical sensors still holds great promise. [196] Similar to how clustering of plasmonic nanoparticles affects the overall optical properties, the clustering of magnetic nanoparticle also leads to changes in the magnetic resonance (MR) signal. It has been shown that during the self-assembly of magnetic nanoparticles, the nanoparticles act as magnetic relaxation switches by causing extensive spinspin relaxation time changes (δT2) of surrounding water molecules.…”
Section: 14mentioning
confidence: 99%
“…Gold nanoparticles (AuNPs), one of the most important representatives of noble metal nanoparticles that exhibit unique optical properties depending on their size and shape, are used in the design of colorimetric sensors and probes with different approaches . The well-known detection principles for aggregation- and antiaggregation-based approaches generally rely on the electrostatic, hydrogen bonding (H-bonding), and electron donor–acceptor interactions between analytes and unlabeled/labeled AuNPs .…”
Section: Introductionmentioning
confidence: 99%
“…The well-known detection principles for aggregation- and antiaggregation-based approaches generally rely on the electrostatic, hydrogen bonding (H-bonding), and electron donor–acceptor interactions between analytes and unlabeled/labeled AuNPs . The color change of the colloidal gold solution associated with aggregation (red-to-blue) or antiaggregation (blue-to-red) may enable naked-eye detection even at picomolar (pM) concentrations because of very high molar absorption coefficients (ε) (10 8 to 10 10 L mol –1 cm –1 ) for AuNPs. , AuNPs, previously employed in the colorimetric determination of many environmentally and biologically important analytes (heavy metal ions, pesticides, pharmaceutical active ingredients, antioxidants, etc), began to be used in the colorimetric detection of nitro-energetic materials at the pM level in 2008 under the leadership of Jiang and his working group . Following this study, many studies based on aggregation/antiaggregation of AuNPs have been published for the detection of energetic substances such as 2,4,6-trinitrophenyl- N -methylnitramine (tetryl), pentaerythritol tetranitrate (PETN), nitroguanidine, and especially TNT. ,, In 2019, development of a ratiometric sensor based on the aggregation of l -cysteine-functionalized gold nanoparticles (Cys-AuNPs) in the presence of Cu II ions for NTO detection was carried out in our laboratories .…”
Section: Introductionmentioning
confidence: 99%